Acute Exercise-Induced Oxidative Stress Does Not Affect Immediate or Delayed Precursor Cell Mobilization in Healthy Young Males - Schmid, Michelle; Gruber, Hans-Jürgen; Kröpfl, Julia M.; Spengler, Christina M. (Frontiers in Physiology, 2020)
Exercise is known to acutely and transiently mobilize precursor cells to the peripheral blood. To date, the underlying mechanisms have not yet been fully elucidated and we hypothesized that exercise-induced oxidative stress could be a mobilizing agent, either directly or via circulating apoptotic cells as mediators. The aim of the study was to assess the effect of acute exercise-induced oxidative stress on numbers of circulating angiogenic (CACs) and non-angiogenic precursor cells (nCACs), mesenchymal precursor cells (MPCs), mature endothelial and mononuclear cells (MNCs), as well as their apoptotic subsets. Healthy, young males (n=18, age: 24.2 ± 3.5 years) completed two identical, standardized incremental cycling tests. The first, un-supplemented control test was followed by a 7-day-long supplementation of vitamin C (1000 mg/day) and E (400 I.U./day), immediately preceding the second test. Blood samples were collected before, directly after, 30, 90, 180, and 270 min after exercise and aforementioned circulating cell numbers were determined by flow cytometry and a hematology analyzer. Additionally, total oxidative (TOC) and antioxidative (TAC) capacities were measured in serum at all timepoints. Antioxidative supplementation abolished the exercise-induced increase in the oxidative stress index (TOC/TAC), and reduced baseline concentrations of TOC and TOC/TAC. However, it did not have any effect on CACs, nCACs and MPC numbers or the increase in apoptotic MNCs following exercise. Our results indicate that exercise-induced oxidative stress is neither a main driver of lymphocyte and monocyte apoptosis, nor one of the mechanisms involved in the immediate or delayed mobilization of precursor cells.